INTERGENERATIONAL LANGUAGE PREFERENCE SHIFT AMONG CEBUANOS ON THE CEBUANO, FILIPINO, AND ENGLISH LANGUAGES - Dreisbach, Jeconiah Louis; Demeterio III, Feorillo Petronilo A. (LLT Journal: A Journal on Language and Language Teaching, 2020)
The historical linguistic conflict of the Cebuano people against the Tagalog-based Philippine national language has been evident in the literature written by Cebuano academics. However, there is no published empirical evidence that presents the on-ground language attitudes of the Cebuanos on the Cebuano, Filipino, and English languages. Employing mixed methods research, the researchers found that both generations predominantly use the Cebuano language for everyday communication. A significant difference was observed in the use of Filipino and English languages as the younger generation spoke it more than the elder counterparts. A language shift was also seen from Cebuano to English on the language used formal communication between the generations. Attitudes on everyday communication revealed that Cebuanos prefer to maintain their mother tongue as the language to be used in speaking with family, friends, relatives, and close people seeing that the younger generation has limited vocabulary on the Cebuano language. Respondents mostly favored English to be the language used for formal communication due to its stature as an international language and its association to high socioeconomic standing. A collective majority from both generations would also like to maintain Tagalog-based Filipino to be the Philippine national language.